Recorded Diagnoses of Depression During United States Delivery Hospitalizations, 2000–2015 - Haight, Sarah C. (Obstet Gynecol, 2019)
OBJECTIVE: To describe national, state-specific, and sociodemographic trends in diagnoses of depressive disorders recorded during delivery hospitalizations. METHODS: Data were analyzed from the National Inpatient Sample (2000–2015) and 31 publically available State Inpatient Databases (2000–2015) of the Healthcare Cost and Utilization Project. Delivery Hospitalizations were identified by using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnostic and procedure codes for obstetric delivery. Depressive disorders were identified from ICD-9-CM diagnoses codes classified as depressive disorders in the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (291.89, 292.84, 293.83, 296.2–296.26, 296.3–296.36, 300.4, and 311). Prevalence rates and average annual rate change were calculated nationally and across 28 states with at least 3 years of data and age, payer source, and race or ethnicity. RESULTS: The U.S. rate of depressive disorders recorded during delivery hospitalizations increased from 4.1 diagnoses per 1,000 hospitalizations in 2000 to 28.7 in 2015. Rates significantly increased in 27 of the 28 states. Recent (2014–2015) rates were lowest in Hawaii and Nevada (<14/1,000) and highest in Vermont, Minnesota, Oregon, and Wisconsin (>49/1,000). Rates in 2015 were highest among those aged 35 years or older, public insurance recipients, and non-Hispanic white women (>31/1,000). The highest annual rate increases were in Vermont and Maine (≥3.8/1,000). Non-Hispanic white women, those ≥ 35 years of age, and public insurance recipients showed the highest annual rate increases during 2000–2015 (≥1.7 per 1,000). CONCLUSION: During 2000–2015, rates of depressive disorders recorded during delivery hospitalizations increased nationally, in 27 states with available data, and across all sociodemographic categories.